Leadership Practices of School Principals in Deaf Schools in the Gaza Governorates in Light of Positive and Motivating Environment Standards: A Case Study - Tanira, Mohammed Othman Musbah; KhalfAlla, Mahmoud E.; Algomasy, Mohammed E. (University of Science and Technology Journal for Management and Human Sciences, 2025)
The study aimed to identify the perceptions of teachers at Mostafa Sadeq Al-Rafii Secondary School for Deaf (Male Students) in the southern governorates of Gaza regarding the leadership practices of the school principal and to explore ways to develop these practices in light of the standards of a positive and motivating environment. The researchers adopted a qualitative approach using a case study methodology. Semi-structured interviews were conducted with (11) teachers at the school, in addition to in-depth interviews with (4) educational experts. Simple exploratory observation was also employed to monitor behaviors within the school. The results classified teachers' opinions into (6) key themes: (clarity of vision and objectives, exemplary leadership, fostering a culture of innovation, communication and interaction, delegation, and support and motivation). Experts’ perspectives on development strategies were also categorized into (6) core ideas: (planning, enhancing leadership capacities, achieving balanced delegation, promoting teachers' professional development, improving the school environment, and establishing partnerships). In light of these findings, the study recommends adopting the experts’ suggestions, conducting periodic follow-ups at the deaf school, encouraging the principal to refine leadership practices, and implementing activities that foster creative potential. These measures would strengthen deaf students' confidence in their academic and practical abilities and contribute to cultivating a positive and motivating environment.
Keywords: leadership practices; school principal; deaf schools; positive and motivating environment